Adolescent Attitudes Towards Drug Abuse - I Made Nursana (Health Notions, 2017)
Drug abuse causes many harm, both materially and non-material, such as death, divorce, robbery, murder and so on. This study aimed to describe the attitude of adolescents to the risk of drug abuse in Toini Village. The subjects were 60 adolescents selected by simple random sampling technique. Data were collected through questionnaires, then analyzed descriptively in the form of frequency distribution. The results showed that 95% of teenagers were positive for substance abuse. Keywords: Attitude, Adolescent, Drugs